2006
DOI: 10.1097/01.fjc.0000205497.90765.b0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Azelnidipine and Other Ca2+-Channel Blockers on the Induction of Inducible Nitric Oxide Synthase in Vascular Smooth Muscle Cells

Abstract: Overproduction of nitric oxide by inducible nitric oxide synthase contributes to the progression of cardiovascular disease. We investigated the effects of azelnidipine and other Ca2+-channel blockers on nitric oxide production by cultured aortic smooth muscle cells isolated from Wistar rats and human umbilical vein endothelial cells (HUVECs), using the Griess reaction and oxyhemoglobin method. Release of lactic dehydrogenase (LDH) was measured to evaluate cell damage, and immunohistochemistry was performed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…There is a general consensus that 1,000 nmol/L CCB is considerably high but this concentration is relevant to a clinical setting because the tissue concentration of azelnidipine is higher than that in the plasma due to its high lipid solubility. 16) Second, we have not yet determined whether this effect is unique to azelnidipine, or if other third-generation DHP-based CCBs have similar effects. In particular, amlodipine is known to exert pleiotropic effects such as inhibition of platelet aggregation and stimulation synthesis, which are distinct from calcium channel antagonism, 14) and therefore its effect on the vascular calcification process should also be examined in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a general consensus that 1,000 nmol/L CCB is considerably high but this concentration is relevant to a clinical setting because the tissue concentration of azelnidipine is higher than that in the plasma due to its high lipid solubility. 16) Second, we have not yet determined whether this effect is unique to azelnidipine, or if other third-generation DHP-based CCBs have similar effects. In particular, amlodipine is known to exert pleiotropic effects such as inhibition of platelet aggregation and stimulation synthesis, which are distinct from calcium channel antagonism, 14) and therefore its effect on the vascular calcification process should also be examined in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, azel-nidipine is reported to cause longer relaxation of smooth muscle cells and more enhanced NO production in endothelial cells than other CCBs. 15,16) Furthermore, we have previously reported that azelnidipine down-regulates gene expression of molecular components of the renin-angiotensin-aldosterone system, 17) suggesting a novel mechanism for the vasoprotective and renoprotective effect of azelnidipine. Despite the potential beneficial effect of azelnidipine on vascular cells, it has not yet been determined whether azelnidipine inhibits the osteogenic differentiation of VSMCs and further development of vascular calcification.…”
mentioning
confidence: 99%
“…CCBs are known to increase NO production through upregulation of eNOS [29,30] . The antioxidative action of a CCB also enhances NO production since NO is rapidly deactivated by ROS [31][32][33] .…”
Section: Discussionmentioning
confidence: 99%
“…While DCCB is regarded to have anti-oxidative activity [7], azelnidipine is expected to have a larger anti-oxidative activity at its clinical dosage than other DCCBs [37]. In the present study, we evaluated the effectiveness of azelnidipine in terms of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%